Interleukin-27 Receptor Limits Atherosclerosis in Ldlr(−/−) Mice - Koltsova, Ekaterina K. (2012)
RATIONALE: Atherosclerosis is a chronic inflammatory disease of the arterial wall. Several proinflammatory cytokines are known to promote atherosclerosis, but less is known about the physiological role of anti-inflammatory cytokines. Interleukin (IL)-27 is a recently discovered member of the IL-6/IL-12 family. The IL-27 receptor is composed of IL-27 receptor A (WSX-1) and gp130 and is required for all established IL-27 signaling pathways. The expression of the IL-27 subunit Ebi3 is elevated in human atheromas, yet its function in atherosclerosis remains unknown. OBJECTIVE: The aim of this study was to test the role of IL-27 receptor signaling in immune cells in atherosclerosis development. METHODS AND RESULTS: Atherosclerosis-prone Ldlr(−/−) mice transplanted with Il27ra(−/−) bone marrow and fed Western diet for 16 weeks developed significantly larger atherosclerotic lesions in aortic roots, aortic arches, and abdominal aortas. Augmented disease correlated with increased accumulation of CD45(+) leukocytes and CD4(+) T cells in the aorta, which produced increased amounts of IL-17A and tumor necrosis factor. Several chemokines, including CCL2, were upregulated in the aortas of Ldlr(−/−) mice receiving Il27ra(−/−) bone marrow, resulting in accumulation of CD11b(+) and CD11c(+) macrophages and dendritic cells in atherosclerotic aortas. CONCLUSIONS: The absence of anti-inflammatory IL-27 signaling skews immune responses toward T-helper 17, resulting in increased production of IL-17A and tumor necrosis factor, which in turn enhances chemokine expression and drives the accumulation of proatherogenic myeloid cells in atherosclerotic aortas. These findings establish a novel antiatherogenic role for IL-27 receptor signaling, which acts to suppress the production of proinflammatory cytokines and chemokines and to curb the recruitment of inflammatory myeloid cells into atherosclerotic aortas.